Factors Influencing Decision-Making for Poststroke Paretic Upper Limb Treatment: A Survey of Japanese Physical and Occupational Therapists - Koichiro Hirayama; Takashi Takebayashi; Kayoko Takahashi (Hindawi-Wiley, 2024)
This study investigated the treatment methods used by physical and occupational therapists for poststroke paretic upper limbs and the factors influencing their decision-making processes. For the treatment methods of poststroke paretic upper limbs, the respondents were asked to select the most clinically used treatment according to the severity of the patient's condition. For the factors influencing their decision-making processes, the respondents were asked to indicate each determinant using a 5-point Likert scale (1 = no influence at all to 5 = very strong influence). Six hundred thirty-eight therapists participated in this study. Exploratory factor analysis was used to assess the validity of the questionnaire. The findings indicated task-specific training (N=333, 52%) as the most popular for mild cases, followed by repetitive facilitative exercise (n=143, 22.3%) for moderate cases and electrical stimulation (n=246, 38.4%) for severe cases. This study revealed that evidence about treatment (very strong: n=171 (27.0%), and strong: n=287 (45.0%)) and patient preferences (very strong: n=203 (31.8%), and strong: n=251 (39.3%)) affected decision-making significantly regarding treatment methods for the poststroke paretic upper limb.